Control of Salmonella in chicken meat using a combination of a commercial bacteriophage and plant-based essential oils. (April 2020) - Moon, Sun Hee; Waite-Cusic, Joy; Huang, En
Abstract: Salmonella contamination in broiler carcasses poses significant health concerns. The objectives of this study were to evaluate the antimicrobial activity of 10 essential oil compounds and to determine the combined effects with a commercial bacteriophage (SALMONELEX) against Salmonella . Thymol and carvacrol were the most active compounds tested, with a minimum inhibitory concentration (MIC) of 0.25–1 mg/ml and a minimum bactericidal concentration (MBC) of 0.5–1 mg/ml against three Salmonella strains. Multiplicity of infection (MOI), or bacteriophage/pathogen ratio (PFU/CFU), significantly affected bacteriophage efficacy in media and in chicken products. The bacteriophage decreased Salmonella Typhimurium JWC-3001 by 5 log CFU/ml at low MOI (≥1.7) in tryptic soy broth, but a higher bacteriophage concentration was needed to exhibit bactericidal effect in chicken products. Dipping of inoculated chicken in 1.6% (w/v) thymol and carvacrol emulsions for 3 min inactivated 1.3 and 1.6 log CFU/g, respectively, of a cocktail of three Salmonella strains. A sequential dipping treatment of inoculated chicken in bacteriophage (1.1 × 10 8  PFU/ml) for 3 min and in 1.6% (w/v) thymol or carvacrol for 3 min resulted in reductions of 1.9–2.0 log CFU/g of the cocktail. The combined treatments resulted in significantly greater reduction of Salmonella than individual bacteriophage or essential oil treatments. Highlights: Thymol and carvacrol are highly active against Salmonella . Bacteriophage (SALMONELEX) showed broad activity against all tested Salmonella strains. Bacteriophage and thymol/carvacrol combinations reduced 1.9–2.0 log Salmonella in chicken.